Visualization of Respiratory Commensal Bacteria in Context of Their Natural Host Environment - Bonifacio, Joao P. P.; Schmolke, Mirco (Frontiers in Microbiology, 2021)
Commensal microbes are an integral component of mammalian physiology. 16S rRNA gene specific next generation sequencing from DNA of total organs or swabs/lavages revolutionized the characterization of bacterial communities in virtually every ecological niche of the body. Culturomics, next allowed the isolation and characterization of commensal bacteria in the lab and the establishment of artificial communities of bacteria, which were eventually reintroduced in model organisms. Spatial organization of microbiota within a given host environment is critical to the physiological or pathological phenotypes provoked by commensal microbiota. In situ hybridization (ISH) is a complementary technique to sequencing and culturing to visualize the presence of individual bacterial operational taxonomic unit (OTUs) in context of the colonized organ. We recently applied highly sensitive in situ RNA hybridization to detection of commensal bacteria in low abundance respiratory tract samples of mice housed under specific pathogen free conditions. This technique allows species-specific detection of living bacteria using RNAScopeTM technology, while preserving the natural environment of the organ. We here provide a detailed step-by-step protocol describing the detection of commensal lung bacteria in respiratory tissue.